Gendered and Racialised Ambiguity: An Exploration of Métisses Women’s Complex Identities and Representations in French-African contexts - Sy, Aliyah Myriam (My University, 2022)
The term métis a French word referring to a person of mixed ancestry - which, for the purposes of this research, will designate a person specifically of ‘black’ and ‘white’ parentage - despite its absence of biological reality, has been used increasingly in the present francophone society where the possibilities of contact between peoples and cultures have multiplied. Representing both an individual and collective experience, it is a complex concept, reflecting a pluralistic and moving reality that not only points out the relationship of each individual to their own history and identity, but also the relations that society maintains with otherness. Whether assumed, rejected, or subject to indifference, the métis identity is thus a major space for reflection on the evolution of today’s multicultural societies. In this context of a moving and evermore dynamic notion of identity, the figure of the métisse woman in particular (whether in literature or society) stands at the crossroads of discourses on race and gender, as well as class and sexuality. The present research therefore aims at offering a non-exhaustive overview of feminine afro-descendant métissage by studying the processes of identity construction, evolution, and representation of this ambiguous figure, with a particular focus on in-betweenness, double consciousness, and sense of belonging. To do so, the study will first rely on literary works from the past centuries, from canons such as Charles Baudelaire’s Les Fleurs du Mal (1857) and Emile Zola’s Thérèse Raquin (1867) to Abdoulaye Sadji’s Nini, mulâtresse du Sénégal (1951) portraying the métisse through the writers’ (male) gaze upon her. Secondly, this study will propose an analysis revolving around the lived experiences of five women of French-African descent using semi-structured interviews. The participants, drawing on their own personal understanding of their identity, were invited to share aspects of their stories, to contrast and assess traditional representations of métisses women. In light of the literature representing the métisse and of the interviews’ findings giving her voice, the present research seeks to interrogate what it means to be a métisse woman and explore how her ambivalent identity is imagined, constructed and experienced as fundamentally intersectional, gendered and racialised.